2021
DOI: 10.1111/epi.16828
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatology of carbamazepine‐ and oxcarbazepine‐induced hyponatremia in people with epilepsy

Abstract: Objective To ascertain whether adverse effects experienced by people taking carbamazepine or oxcarbazepine could be attributed to carbamazepine‐ or oxcarbazepine‐induced hyponatremia (COIH). Methods We performed an observational study, collecting data between 2017 and 2019 on serum sodium levels and adverse effects retrospectively in people with epilepsy while receiving treatment with either carbamazepine (CBZ) or oxcarbazepine (OXC). We defined hyponatremia as sodium level ≤134 mEq/L and severe hyponatremia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…16 Acute symptomatic seizures, dizziness, tiredness (fatigue), instability, and diplopia have been reported more often in hyponatremia groups than in patients with normal levels of sodium. 17 In the current study, seizure (4.5%), hyponatremia (4.2%), dizziness (2.7%), rash (2.5%), and fatigue (2.5%) were also among the most common AEs identified.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…16 Acute symptomatic seizures, dizziness, tiredness (fatigue), instability, and diplopia have been reported more often in hyponatremia groups than in patients with normal levels of sodium. 17 In the current study, seizure (4.5%), hyponatremia (4.2%), dizziness (2.7%), rash (2.5%), and fatigue (2.5%) were also among the most common AEs identified.…”
Section: Discussionsupporting
confidence: 47%
“…The safety profile observed in this long‐term PMS analysis supports the results from a previous worldwide 6 years PMS analysis, 16 in which the most commonly identified AEs were hyponatremia (10.2%), seizure (5.8%), dizziness (4.1%), rash (2.6%), fatigue (2.1%), and nausea (1.8%) 16 . Acute symptomatic seizures, dizziness, tiredness (fatigue), instability, and diplopia have been reported more often in hyponatremia groups than in patients with normal levels of sodium 17 . In the current study, seizure (4.5%), hyponatremia (4.2%), dizziness (2.7%), rash (2.5%), and fatigue (2.5%) were also among the most common AEs identified.…”
Section: Discussionmentioning
confidence: 99%
“…CBZ has been increasingly demonstrated to cause hyponatremia, which mimics the syndrome of inappropriate antidiuretic hormone secretion [ 11 , 12 , 13 , 14 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 27 ]. Esaxerenone, known to be a nonsteroidal mineralocorticoid receptor blocker, was demonstrated to modify the magnitude and gating of I Na [ 38 ], while sparsentan, a dual antagonist of endothelial type A receptor and angiotensin II receptor, could suppress I Na [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of additional notice, although CBZ is safe and effective in anti-convulsant activities, the unwanted events following CBZ treatment, such as hyponatremia, QT-interval prolongation, hyperprolactinemia, change in pitch perception and idiosyncratic reactions, have gradually emerged [ 5 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The effectiveness of CBZ in inhibiting the activity of ATP-sensitive K + (K ATP ) channels has also been demonstrated [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was analyzed in a previous study where 1370 patients treated with CBZ or OXC were identified, 410 of whom had at least one episode of hyponatremia. Authors found that adverse effects (dizziness, tiredness, instability, and diplopia) occurred in 65% of participants with hyponatremia compared to 21% with normal sodium levels (odds ratio 7.5, p ≤ 0.001) and in 83% of people with severe hyponatremia compared to 55% in those with mild hyponatremia ( p ≤ 0.001) [ 18 ]. Previous studies also found that even mild chronic hyponatremia can cause neurocognitive deficits and gait disturbance falls, and the treatment of this disturbance of electrolytes improved neurocognitive and neuromuscular function [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%